Religious appreciation and psychological well-being among Malaysian army - Wan Othman, Wan Norhayati; Zainudin, Zaida Nor; Che Amat, Muhammad Asyraf; Omar Mokhtar, Muhammad Yassin (Human Resource Management Academic Research Society, 2020)
The purpose of this study is to analyze the differences in the psychological well-being of Malaysian Army based on demographic factors and to determine the relationship between religious appreciation and psychological well-being of Malaysian Army. The study was conducted using a quantitative method which is a survey study where the questionnaire was distributed to the study samples. The sample of this study is 3,000 Malaysian Army using random group method. The instruments in this study consist of the Religious Appreciation Scale (RAS) and the Psychological Wellbeing Scale (PSWS). The reliability coefficients of these scales using Cronbach's alpha analysis found that over .70. The findings show that no significant difference in the psychological well-being of Malaysian Army based on marriage status variables. While for academic qualification and rank variables show significant differences in psychological well-being. The results of the study also found that the religious appreciation factor had a significant positive relationship with the psychological well-being of Malaysian Army.